Efficacy of seed dressing pesticides on emergence and seedling characters of cotton in root-knot nematode infested soil - R.A. DHOOT, B.P. KURUNDKAR and (Indian Phytopathology, 2002)
Although reduction in root-knot nematode infestation by seed dressing with systemic pesticides has been reported, not much work has been done in India on this aspect of cotton crop. Therefore, the present study was conducted to see the efficacy of four systemic pesticides as seed dressers to cotton (hybrid NHH-44) in root-knot (Meloidogyne incognita) infested soil.